2016
DOI: 10.1016/j.compstruct.2015.12.037
|View full text |Cite
|
Sign up to set email alerts
|

On quantifying the effect of noise in surrogate based stochastic free vibration analysis of laminated composite shallow shells

Abstract: This paper presents the effect of noise on surrogate based stochastic natural frequency analysis of composite laminates. Surrogate based uncertainty quantification has gained immense popularity in recent years due to its computational efficiency. On the other hand, noise is an inevitable factor in every real-life design process and structural response monitoring for any practical system. In this study, a novel algorithm is developed to explore the effect of noise in surrogate based uncertainty quantification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 31 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…The effective elastic properties of the individual lamina are obtained using Eq. (17). Thus, the natural frequency problem can be stated as = ( , , , , , 1 , 2 , … .…”
Section: Uncertainty Analysis Of Natural Frequencies Of a Ud Flax /Epmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective elastic properties of the individual lamina are obtained using Eq. (17). Thus, the natural frequency problem can be stated as = ( , , , , , 1 , 2 , … .…”
Section: Uncertainty Analysis Of Natural Frequencies Of a Ud Flax /Epmentioning
confidence: 99%
“…Instead, surrogate model approaches, which are constructed based on a limited set of actual input/output data points, are a suitable method when dealing with such complex problems. Several methods of application of surrogate models have been reported in the literature for evaluation of uncertainties in composite laminates, such as Kriging method [15,16], radial basis function [17], polynomial chaos expansion (PCE) [18][19][20], and artificial neural network (ANN) [21,22]. State-of-the-art reviews on the surrogate models for evaluating the uncertainty in structural responses of composite laminates can be found in [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the actual field vibration measurements may suffer from certain unavoidable errors, which make the damage identification process even more difficult. There is substantial amount of literature available dealing with the issue of noise in different SDI techniques and other engineering problems (Aiko et al, 2006;Cao et al, 2014;Dey et al, 2016b;Li and Law, 2008;Mukhopadhyay et al, 2016;Udwadia, 2005). These studies consider primarily the uncertainties associated with system parameters and measurement noise in SDI.…”
Section: Performance Of Rs-hdmr-based Damage Identification Algorithmmentioning
confidence: 99%
“…Stochastic natural frequency of noise-induced support vector regression (SVR) model for laminated composite curved panels is analysed by Dey et al [49]. The effect of noise in surrogate model is quantified by Mukhopadhyay et al [50], whereas Dey et al [44] presented the effect of noise using polynomial neural network approach in uncertainty quantification of natural frequency, and Chakraborty [51] predicted delamination in laminated composite using ANN approach. Lee et al [52] determined the equivalent material properties of glass/epoxy composite by applying the homogenization method, and stochasticity in the equivalent material properties are assessed by MCS and found that variation in individual material properties has a significant effect on the equivalent material properties.…”
Section: Introductionmentioning
confidence: 99%